PENGAKUAN DIRI NARAPIDANA ATAS HASIL PEMASYARAKATAN SERTA IMPLIKASINYA PADA SIKAP JERA DAN KEINGINAN RESOSIALISASI - Bambang Slamet Riyadi (Universitas Nasional, 2016)
This account is made on the ground that in the past, beginning 1964, the goal of rehabilitating or re-educating prisoners were not satisfactorily achieved. The problem statement of the study is to see the extent of success of rehabilitation programmes. The method used in the study is a comparative study by comparing the plan on rehabilitation program and its implementation and its impact on the prisoners’ response to the program. The hypothesis that the six variables (rehabilitation program, the jury’s decision, the prisoners’s religious devoutness, the desire to live normal life,the respect of family life, and self-actualization simultaneously affect perceived success of rehabilitation program; wahereas the hypothesis 2 the same six variables above partially affect prisoners recognition of thesuccesss of the program.